HAK WARIS ANAK DILUAR NIKAH PERSFEKTIF HUKUM ISLAM DAN PERDATA - Widhy Andrian Pratama; Adis Nevi Yuliani; Djulya Eka Pusvita; Murdiono Murdiono (Fakultas Hukum Universitas Wiraraja, 2025)
An illegitimate child refers to a child born from a relationship outside of a legal marriage at a certain time. The status and position of the child are highly dependent on the legality of the marriage of his parents. Based on National Law, a marriage is considered valid if it is registered by an authorized institution or agency. A child born out of wedlock only has a legal relationship with his mother and is entitled to inherit property from the mother's side. If the child's blood relationship with his biological father is severed, then the child's inheritance rights only apply to the mother's family, and not to the biological father's family. Therefore, an illegitimate child is not entitled to receive an inheritance from his biological father. However, this provision only applies in terms of the distribution of inheritance to illegitimate children. The recipient of the inheritance is an individual who has legal inheritance rights, such as Zawil Khurd and Zawir Alham. This article adopts a normative research approach, which utilizes literature and books as sources to analyze doctrine from a normative perspective. In the study of normative law, the main focus lies on understanding the essence and scope of law as a system that studies reality. This discipline involves two aspects, namely analytical and normative, with law included in this category. It can be concluded that illegitimate children have the right to inherit together with heirs from groups I, II, III, or IV, and can receive inheritances even though they come from groups with different degrees. However, in certain situations, if heirs from groups I to IV do not leave descendants and there are only illegitimate children, then the legitimate illegitimate children are recognized as heirs who have the right to receive all inheritance, in accordance with the provisions of Article 865 of the Civil Code. In marriage law, the legal status of illegitimate children is regulated by Law Number 1 of 1974, specifically Article 43 paragraph (1), which states that illegitimate children only have a civil relationship with their mother and family. Therefore, illegitimate children are only legally bound to their mother and family, without any legal relationship with the father who raised them.